Association between functional CD24 polymorphisms and susceptibility to autoimmune diseases: A meta-analysis - Lee, Y H; Bae, S-C (Cellular and Molecular Biology, 2015)
This study aimed to explore whether the functional CD24 A57V and TG/del polymorphisms are associated with susceptibility to autoimmune diseases. A meta-analysis was conducted on the associations between the CD24 A57V and TG/del polymorphisms and autoimmune diseases using (1) allele contrast, and (2) the recessive, (3) dominant, and (4) co-dominant models. Twenty-six comparative studies with 7,507 patients and 8,803 controls were included in the meta-analysis. The meta-analysis revealed a significant association between autoimmune disease and the CD24 Val allele (OR = 1.285, 95% CI = 1.177–1.403, p = 1.0 í— 10-9). Meta-analysis by autoimmune disease type showed a significant association between the CD24 Val allele and multiple sclerosis (MS) (OR = 1.420, 95% CI = 1.239–1.628, p = 4.7 í— 10-8) and systemic lupus erythematous (SLE) (OR = 1.282, 95% CI = 1.081–1.521, p = 0.004), but not Crohn's disease (CD) (OR = 1.003, 95% CI = 0.826–1.218, p = 0.974). Meta-analysis of the CD24 Val/Val genotype showed an association with ulcerative colitis (OR = 1.778, 95% CI = 1.148–2.753, p = 0.010). In addition, meta-analysis by autoimmune disease type revealed a significant association between the CD24 TG-deletion allele and MS (OR = 0.596, 95% CI = 0.415–0.856, p = 0.005) and CD (OR = 1.594, 95% CI = 1.175–2.161, p = 0.003). This meta-analysis indicates that the functional CD24 A57V and TG/del polymorphisms are associated with susceptibility to multiple autoimmune diseases including SLE, MS, UC and CD.